Impact of recommissioning flushing on Legionella pneumophila in a large building during the COVID-19 pandemic - Grimard-Conea, Marianne; Deshommes, Elise; Doré, Evelyne; Prévost, Michèle (Frontiers in Water, 2022)
COVID-19 shutdowns drastically increased the frequency and duration of water stagnation events in building plumbing systems, urging local authorities to issue guidance for the safe reopening of buildings mostly by recommissioning flushing. The objectives of this study were to document the dynamic changes of bacterial indicators (adenosine triphosphate [ATP], total and intact cell counts [TCC, ICC]) and the prevalence of Legionella pneumophila (Lp) in 20-21 showerheads in a large building before (16-week building closure) and then shortly (24 h) and monthly (4-week of distal water stagnation) after targeted recommissioning flushing. Following the 16-week shutdown, the highest mean of ATP (10 pg ATP/mL), TCC (1.7 X 106 count/mL) and ICC (5.2 X 105 count/mL) were measured in first draw samples. This bacterial amplification was mostly attributable to detachment from biofilm present in the distal devices and immediate connecting piping. Culture-based (mean of 4 487 MPN/L) and quantitative polymerase chain reaction (qPCR) (mean of 63 822 gu/L) concentrations of Lp were respectively measured in 81% and 90% of first draw samples. Individual flushing of showerheads for five minutes resulted in 1.2-278-fold decreases in ATP, whereas TCC and ICC were lowered by 1.1- and 0.7-log on average. A one-log reduction in culture-based and qPCR Lp was only achieved in 63% and 29% of paired water samples, resulting in less than one-log reduction in mean risk values per exposure, thus demonstrating the limited effects of fixture-flushing for risk reduction. Clear short-term (24 h) benefits of device recommissioning flushing included lowered values of all bacterial indicators and Lp levels systematically under the common alert threshold of 1 000 MPN/L in first draws. However, after a period of one month without water use, these benefits were mostly lost with considerable rebounds of concentrations to similar levels than those measured following the 16-week building closure. Results highlight the temporary benefits of device recommissioning flushing for the control of Lp in shower systems, especially in buildings colonized by Legionella.